Properties of ZnO:Mn Nanoparticles Immobilized in Polyethylene Matrix - Lashkarev, G.V.; Demydiuk, P.V.; Yurkov, G.Yu.; Dmitriev, O.I.; Bykov, O.I.; Klochkov, L.I.; Pyratinskiy, Yu.P.; Slynko, E.I.; Khandozhko, A.G.; Popkov, O.V.; Taratanov, N.A. (Наносистеми, наноматеріали, нанотехнології, 2010)
ZnO:Mn nanoparticles (of 3—5 nm) immobilized in polyethylene matrix are synthesized. The samples with different content of the manganese (5%, 10%, and 20% of initial solution of Mn and Zn precursors) are investigated by means of ESR, PL, and XRD. Thus, the behaviour of the Mn impurities in ZnO is studied. As revealed, the most of the manganese in ZnO forms the second undetermined phase MnOx or substitute zinc in cation sublattice at the surface layer of the nanoparticles. The value of constant of hyperfine structure of Mn is higher than an expected one (|A| = 89.5⋅10−4 cm−1
that is significantly differ from the constant of hyperfine structure of Mn incorporated
into ZnO single crystal (76⋅10−4 cm−1)). Photoluminescence measurements reveal wide band of emission in green—red region (500—600 nm), with different position of the maximum depending on the manganese content. Одержано наночастинки ZnO:Mn розмірами 3—5 нм. За допомогою метод ЕПР, рентґеноструктурної аналізи та фотолюмінесценції досліджувалася структура цих наночастинок з різним вмістом мангану: 5%, 10% та 20% масової частки по відношенню до вихідного розчину прекурсорів. Було показано, що переважна кількість мангану формує другу фазу та заміщує цинок у катіонній підґратниці в поверхневому прошарку цих наночастинок. Значення надтонкої структури в ЕПР-дослідженнях виявилися більшими за очікуване (|A| = 89,5⋅10−4 см−1, що значно відрізняється від довідникових даних константи надтонкої структури для мангану в кристалічній ґратниці ZnO – 76⋅10−4 см−1). Фотолюмінісцентні міряння виявили широку лінію випромінення в зелено-червоній області спектру 500—600 нм з різним положенням максимуму (залежно від типу зразка). Получены наночастицы Zno:Mn размерами 3—5 нм. С помощью методов ЭПР, рентгеноструктурного анализа и фотолюминесценции исследовалась структура этих наночастиц с разным содержимым марганца: 5%, 10% и 20% массовой части по отношению к исходному раствору прекурсоров. Было показано, что преобладающее количество марганца формирует вторую фазу и замещает цинк в катионной подрешетке в поверхностной прослойке этих наночастиц. Значение сверхтонкой структуры в ЭПР-исследованиях оказались больше ожидаемых (|A| = 89,5⋅10−4 см−1, что значительно отличается от справочных данных константы сверхтонкой структуры для марганца в кристаллической решетке ZnO – 76⋅10−4
см−1). Фотолюминесцентные измерения выявили широкую линию излучения в зелено-красной области спектра 500—600 нм с разным положением максимума (в
зависимости от типа образца).